Spin-phonon interaction in transition-metal difluoride antiferromagnets: Theory and experiment - Cottam, M.G.; Lockwood, D.J. (Физика низких температур, 2019)
An overall comparative study is made of the spin-phonon interactions in several rutile-structure transition-metal difluorides, specifically FeF₂, MnF₂, NiF₂, and CoF₂, in terms of recent developments obtained experimentally using inelastic light scattering spectroscopy and theoretically using a modified mean-field approach to estimate spin-pair correlation functions. New experimental data are presented here and interpreted within an extended and comprehensive theoretical treatment to yield estimates for the spin-phonon coupling coefficients and the relative magnitudes of the magneto-optical coupling coefficients.